(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Human Rights, in fact, are fundamental to our nature and affect our daily lives in various ways. Human Rights define the values and worth of each person. We all are equally entitled to our human rights without discrimination. The paper deals with the human and fundamental rights in India. The paper is attempt to analyse the Constitutional provisions and laws in India for the protection of Fundamental Rights. The paper is also discussed about the role of judiciary and Human Rights Commission (NHRC) for the enforcement of Fundamental rights. Human rights belong to everyone and necessary for the development of human beings.